1998
DOI: 10.1016/s0014-5793(98)00217-8
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of a novel 26‐kDa serine protease in the yellow body of Sarcophaga peregrina (flesh fly) pupae

Abstract: We have reported a novel serine protease produced by Sarcophaga peregrina (Nakajima et al., J. Biol. Chem. 272 (1997) 23805^23810). This 26-kDa protease showed antibacterial activity against several bacteria. This activity was an intrinsic characteristic of the enzyme protein and not directly related to its protease activity, because treating the 26-kDa protease with diisopropyl fluorophosphate had no appreciable effect on its antibacterial activity. Unlike bovine trypsin, the 26-kDa protease interacted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…gambiae . Studies that deal with the immune system of insects during metamorphosis show increased anti-bacterial activities [53,54]. However, there is not much information about anti-fungal activity.…”
Section: Discussionmentioning
confidence: 99%
“…gambiae . Studies that deal with the immune system of insects during metamorphosis show increased anti-bacterial activities [53,54]. However, there is not much information about anti-fungal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Further researchers Wang et al 2001;Lin et al 2006;Jitvaropas et al 2009) also observed that the SP homologues from various crustacean species have the antibacterial activity against both gram-negative and gram-positive bacteria. Tsuji et al (1998) found that a 26 kDa SP from flesh fly Sarcophaga peregrina was toxic to the following bacteria and yeasts: S. aureus, Corynebacterium bovis, B. subtilis, E. coli, Salmonella typhi, Candida albicans and Candida pseudotropicalis. Another SP isolated from haemocytes of the mud crab, Scylla paramamosain, could bind to a number of bacteria and bacterial cell wall components (Zhang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Among the insect proteases with high sequence similarity to p37k, the 26-kDa protease of the flesh fly, S. peregrina, is the only example of which the function and expression pattern have been studied. This 26-kDa protease has antibacterial activity and may play a role in immune reaction in the midgut during the pupal stage; however, involvement in midgut degeneration has also been suggested (Nakajima et al, 1997;Tsuji et al, 1998). In the molecular phylogenetic tree of these serine proteases that share relatively high sequence similarity with p37k, five proteins are grouped together with p37k to form an isolated cluster (box in Fig.…”
Section: Phylogenetic Analysis Of P37kmentioning
confidence: 99%
“…In addition to cathepsins and MMPs, serine proteases have also been suggested their involvement in midgut remodeling based on their localization and stage-dependent expression. A 26-kDa serine protease of the flesh fly, Sarcophaga peregrina, appears in the yellow body of pupae in the period of disintegration of the larval midgut (Nakajima et al, 1997;Tsuji et al, 1998). SeCT34 of the Lepidopteran insect, Spodoptera exigua, is a chymotrypsin-type serine protease that is expressed only in the larval midgut just before the onset of pupation (Herrero et al, 2005).…”
Section: Introductionmentioning
confidence: 99%